2008
DOI: 10.1103/physrevlett.101.126101
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Delocalization of Molecular Hydrogen in Alkali-Graphite Intercalates

Abstract: The adsorption of molecular hydrogen (H 2 ) in the graphite intercalation compound KC 24 is studied both experimentally and theoretically. High-resolution inelastic neutron data show spectral features consistent with a strong pinning of H 2 along a single axis. First-principles calculations provide novel insight into the nature of H 2 binding in intercalates but fail to account for the symmetry of the H 2 orientational potential deduced from experiment. The above discrepancy disappears once the H 2 center of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 33 publications
4
41
0
1
Order By: Relevance
“…16 We had previously benchmarked the density functional calculations to more accurate coupled cluster calculations. 16 Consistent with inelastic neutron scattering spectra of H 2 adsorbed to a graphite intercalation compound, KC 24 , 17 we found that, at 0 K, there was quantum delocalisation of the H 2 molecule and, consistent with previous theory 18 and experiment, 19 the zero point energy difference upon binding is a significant fraction of the electronic binding energy, in this case 35 %. 20 We also found that the "helicopter" and "ferris wheel" motions of the adsorbed H 2 molecule were significantly anharmonic and could be modelled as free and hindered rotors, respectively.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…16 We had previously benchmarked the density functional calculations to more accurate coupled cluster calculations. 16 Consistent with inelastic neutron scattering spectra of H 2 adsorbed to a graphite intercalation compound, KC 24 , 17 we found that, at 0 K, there was quantum delocalisation of the H 2 molecule and, consistent with previous theory 18 and experiment, 19 the zero point energy difference upon binding is a significant fraction of the electronic binding energy, in this case 35 %. 20 We also found that the "helicopter" and "ferris wheel" motions of the adsorbed H 2 molecule were significantly anharmonic and could be modelled as free and hindered rotors, respectively.…”
Section: Introductionsupporting
confidence: 72%
“…21 In this paper we extend our 0 K calculations to finite temperature; in the long term, room temperature H 2 storage is required if H 2 is to become a viable alternative to fossil fuels in vehicles. Moreover, the experimental characterisation of putative H 2 storage materials typically takes place between 77 and 98 K. 22 Although quantum effects become less important as temperature increases, H 2 is known to exhibit quantum behaviour at ambient temperature, 17,19 and thus a quantum rather than classical formalism is required. Anharmonicity will become more important as temperature increases, especially for a weakly bound system such as H 2 -Li + -benzene and thus an accurate PES is also required.…”
Section: Introductionmentioning
confidence: 99%
“…A similar adsorption isotope effect has been reported also for graphene, which has been interpreted in terms of similar quantum-mechanically nuclear arguments (Paris et al, 2013). Lovell et al (2009) have studied the room-temperature adsorption of H 2 in the graphite intercalation compound KC 24 with inelastic neutron scattering techniques. By comparing their experimental data to the results of quantum first-principles simulations, they have concluded that QNE are responsible for a tremendous reduction of ∼ 60 % in the amount of taken gas.…”
Section: Carbon-based Crystals and Nanomaterialsmentioning
confidence: 90%
“…The present TASSE measurements also represent a two-order-of-magnitude improvement over the highest spectral resolution reported to date in neutron studies on bulk and adsorbed H 2 using the IRIS spectrometer at the ISIS Facility, United Kingdom. [25][26][27] These previous works were able to attain spectral widths of ∼100 μeV at an energy transfer of 15 meV, and are representative of the current limits of resolution using non-spin-echo neutron spectroscopy.…”
Section: Discussionmentioning
confidence: 99%